Piloting a brief assessment to capture consumption of whole plant food and water: version 1.0 of the American College of Lifestyle Medicine Diet Screener (ACLM Diet Screener) - Karlsen, Micaela C.; Staffier, Kara L.; Pollard, Kathryn J.; Cara, Kelly C.; Hulit, Sarah M.; Campbell, Erin K.; Friedman, Susan M. (Frontiers in Nutrition, 2024)
Background: Despite the availability of various dietary assessment tools, there is a need for a tool aligned with the needs of lifestyle medicine (LM) physicians. Such a tool would be brief, aimed at use in a clinical setting, and focused on a ‘food as medicine’ approach aligned with recommendations for a diet based predominately on whole plant foods. The objective of this study is to describe the development and initial pilot testing of a brief, dietary screener to assess the proportion of whole, unrefined plant foods and water relative to total food and beverage intake. Methods A multidisciplinary study team led the screener development, providing input on the design and food/beverage items included, and existing published dietary assessment tools were reviewed for relevance. Feedback was solicited from LM practitioners in the form of a cross-sectional survey that captured information on medical practice, barriers, and needs in assessing patients’ diets, in addition to an opportunity to complete the screener and provide feedback on its utility. The study team assessed feedback and revised the screener accordingly, which included seeking and incorporating feedback on additional food items to be included from subject matter experts in specific cultural and ethnic groups in the United States. The final screener was submitted for professional design, and scoring was developed. Results Of 539 total participants, the majority reported assessing diet either informally (62%) or formally (26%) during patient encounters, and 73% reported discussing diet with all or most of their patients. Participants also reported facing barriers (80%) to assessing diet. Eighty-eight percent believed the screener was quick enough to use in a clinical setting, and 68% reported they would use it. Conclusion The ACLM Diet Screener was developed through iterative review and pilot testing. The screener is a brief, 27-item diet assessment tool that can be successfully used in clinical settings to track patient dietary intakes, guide clinical conversations, and support nutrition prescriptions. Pilot testing of the screener found strong alignment with clinician needs for assessing a patient’s intake of whole plant food and water relative to the overall diet. Future research will involve pilot testing the